TEMBANG (LAGU) DOLANAN ANAK SEBAGAI INSPIRASI PENCIPTAAN TARIAN ANAK - Untung Muljono (Institut Seni Indonesia Yogyakarta, 2017)
Tembang Dolanan Anak is a creation (fruit of thought) or the composition of the language with the rules of the standard (gumathok) which way of reading it must be dilagukan by using the beauty of sound owned. Tembang (sekar) Java is divided into two categories, namely classic and folk type. The classical tembang is a tembang whose source is from the Javanese royal court from the time of Kediri to Mataram Islam (Yogyakarta and Surakarta), therefore the rules are very strict. The song that developed in the people's circle (in the Hindu era belongs to the caste of waisya and sudra) the mention is